(untitled) (Research, Society and Development, 2025)
Natural food for dogs and cats has become a well-established alternative to industrialized food, and is considered a healthier and more balanced option for pets. This study aims to describe and analyze the effects of natural food for dogs and cats, highlighting its application as an alternative to conventional nutrition based on industrialized food. The specific objectives involve describing the main natural diets, identifying the care needed to ensure nutritional balance, and analyzing the applicability of this approach in the routine of pet owners. Its benefits and challenges are analyzed, especially with regard to animal health and well-being. Among the positive effects observed, we highlight improved digestion, reduced allergic reactions, strengthened immune systems, and a possible increase in the longevity of pets. We also emphasize the importance of veterinary monitoring in order to prevent nutritional deficiencies and ensure food safety. The proposed reflection seeks to raise awareness among pet owners about the benefits and limitations of natural food, aiming to promote adequate nutrition and improve the quality of life of animals.